1996
DOI: 10.1111/j.1476-5381.1996.tb15234.x
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of neutrophils by intrapleural injection of tumour necrosis factor, interleukin‐1, and interleukin‐8 in rats, and its modification by actinomycin D

Abstract: To assess in vivo chemotactic activity of tumour necrosis factor (TNF), interleukin‐1 (IL‐1), IL‐8, and cytokine‐induced neutrophil chemoattractant (CINC), we injected these cytokines into the pleural cavity of rats. CINC (0.1‐1 μg) and recombinant human IL‐8 (rhIL‐8, 0.2–5 μg) caused neutrophil infiltration into the rat pleural cavity in a dose‐dependent fashion, peaking at 3 h. The number of leukocytes in the peripheral blood did not change significantly. RhTNFα and rhIL‐1α also induced neutrophil accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
(19 reference statements)
1
11
0
Order By: Relevance
“…In the present study, intranasal instillation of human recombinant IL-8, which is a strong chemoattractant for rat neutrophils, 22 the 5 rats examined. The fact that epithelial mucus production was observed only in neutrophil-infiltrating epithelia suggests that neutrophils themselves stimulate epithelial mucus production.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, intranasal instillation of human recombinant IL-8, which is a strong chemoattractant for rat neutrophils, 22 the 5 rats examined. The fact that epithelial mucus production was observed only in neutrophil-infiltrating epithelia suggests that neutrophils themselves stimulate epithelial mucus production.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments using the synthetic PIF-core peptide support this conclusion in that proliferation of a similar magnitude was observed. The bell-shaped dose-response curve following Huh7 treatment with synthetic PIF-CP is characteristic of biological responses to several cytokines and growth factors including IFN-γ, IL-6, IL-8 and TNF-α (30)(31)(32)(33). It has also been suggested that bell-shaped dose-response curves may result from the action of an agonist on two separate receptors (34).…”
Section: Discussionmentioning
confidence: 99%
“…The IL-8 concentration also correlates with the neutrophil counts in human pleural effusions [26]. Direct intrapleural injection of IL-8 caused neutrophil infiltration into the pleural cavity in rats in a dose-dependent manner [6]. Conversely, addition of IL-8 antibodies neutralised neutrophil chemotaxis [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Intrapleural injection of talc stimulates a rapid increase in IL-8 in the pleural cavity and an associated influx of polymorphonuclear cells in both human and animal studies [4][5][6]. Pain and fever, which commonly complicate pleurodesis, are believed to result from the pleural inflammation.…”
mentioning
confidence: 99%